EFEKTIVITAS KERJA APARATUR SIPIL NEGARA (ASN) DIMASA PANDEMI COVID 19 (STUDI DI BADAN KESATUAN BANGSA DAN POLITIK DAERAH PROVINSI SULAWESI UTARA) - ANDINI PRASISIA RIWAYAT; JOHNNY POSUMAH; NOVVA PLANGITEN (Sam Ratulangi University, 2022)
The National Unity and Politics Agency is one of the Regional Apparatuses established based onthe Regional Regulation of North Sulawesi Province Number 6 of 2011 concerning theOrganization and Work Procedures of the Inspectorate, Regional Development PlanningAgency, Regional Technical Institutions and Other Institutions, including the Establishment ofthe National Unity and Regional Political Agency North Sulawesi Province. Efforts to increasethe effectiveness of employees at the Regional Political and National Unity Agency of NorthSulawesi Province have been carried out by utilizing existing human resources. The aim is toimprove the effective and efficient governance of the National Unity and Political Agency inorder to improve public services and also improve aspects of civil liberties and aspects of politicalrights. This study was conducted to explain the effectiveness of the work of the State CivilApparatus during the Covid-19 Pandemic at the Regional Political and National Unity Agencyof North Sulawesi Province.Keywords : Work Effectiveness, State Civil Apparatus, Covid-19 Pandemic.